PENENTUAN AKTIVITAS AMILASE DARI UMBI BENGKUANG (Pachyrrizus arosus L.Urb) HASIL EKSTRAKSI DENGAN ETANOL DAN AMMONIUM SULFAT - Iswendi, Iswendi (IAIN Batusangkar, 2010)
This research aimed to determine the optimum amylase activity at the variations of temperature and pH, and the effectiveness of extractors. The extraction of the enzyme can be done in two ways, with an organic solvent and inorganic salt. We have conducted research on amylase activity of yam tubers extracted with ethanol and ammonium sulfate. This research is an experimental research using complete randomized design with two factorials which are pH and temperature. pH variations were 4, 4.5, 5.0, 5.5, and 6, while the variation of temperature are 300 C, 400 C, 500C, and 600C. Isolation of amylase-was carried out by multilevel fractionation using saturated ammonium sulphate 40, 60. 80, and 90% w/v and cold ethanol 95%. Amylase activity was determined based on the concentration of glucose which is result of hydrolysis of starch by Nelson-Somogy method. The highest activity was found in fraction I, pH 4 and temperature of 500C with 34.55 units of activity for ethanol solvent and 30.72 units for ammonium sulfate. Key words: amylase, activity, isolation, yam tubers extracted